Optimasi Teknik Perbanyakan Vegetatif melalui Okulasi pada Jeruk Citrus spp dan Grafting pada Alpukat Persea americana Mill untuk Peningkatan Kualitas dan Produktivitas Tanaman Hortikultura - Allifa Khoerurrahmah; Anggi Agustin; Fathin Dhiya Amani; Feby Nurul Asri M; Mohammad Haris Musthofa (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2025)
Vegetative propagation is a crucial technique in horticultural cultivation aimed at improving plant quality and productivity. This study explores budding in citrus (Citrus spp.) and grafting in avocado (Persea americana Mill.) as methods of plant propagation. Budding involves attaching buds from superior varieties to compatible rootstocks, whereas grafting unites scions and rootstocks to obtain desirable traits. The research was conducted at the Horticulture Seed Center, observing the growth and success of plant unions. The results demonstrate that both techniques effectively enhance plant quality, with budding showing faster results in citrus and grafting improving avocado resilience to environmental conditions. This study provides guidance for farmers to select optimal propagation methods tailored to their plants' specific needs.